The Role of Environmental, Social, and Governance (ESG) on Financial Performance - Sienly Veronica; Ida Ida (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this research is to test and analyze the relationship between Environmental, Social and Governance (ESG) and financial performance. The variables used in this research are Environmental, Social, and Governance as independent variables with the dependent variable being financial performance, which is proxied by ROA, ROE, and ROCE. The sampling technique used was non-probability sampling, purposive sampling so that there were 21 companies registered on Kompas 100 as samples observed from 2017 to 2022. The data analysis method in this research used Spearman correlation. The results of the Spearman correlation test inform that environmental is related to financial performance, which is proxied by ROE, ROA, and ROCE. Social and ROE have a relationship and have no relationship with ROA and ROCE. Governance and ROA are related but not ROE and ROCE. Based on these results, companies must continue to pay attention to and strive to implement ESG so that in the long term they can improve their financial performance.